Peran Guru PAI pada Pembelajaran Aqidah Akhlak dalam Membentuk Moral Peserta Didik di MA NW Keruak: The Role of PAI Teachers in Learning Aqidah Morals in Shaping Students' Morals at MA NW Keruak - Sarudin Efendi; Ahmad Jalaludin; Susi Apriudianisti; Maharani (Pendidikan Al-Gafari, 2026)
This study was conducted with the aim of knowing the importance of the role of Islamic Religious Education Teachers in the formation and development of morals of students at MA NW Keruak. This study is a qualitative study, data collection techniques using observation, interview and documentation methods. The subjects of this study are Islamic Religious Education Teachers which include Teachers of Aqidah Akhlak, Qur'an Hadith, Fiqh and SKI. Based on the results of the study that: First to know the role of Islamic Religious Education Teachers in the formation of morals of students at MA NW Keruak School, it has been carried out very well. There are several roles carried out by teachers, including: 1) Teachers as facilitators. 2) Teachers as directors. 3) Teachers as motivators 4) Teachers as educators. And as for several strategies carried out in the formation of morals of students, one of which is by holding discussion methods and case studies that can be studied and understood directly by students about complex moral situations. And it cannot be separated from several supporting and inhibiting factors, including the teacher's strong intention and motivation in educating and guiding students and the presence of students who do not live with both parents, which makes it a little difficult for teachers to approach students because their characters are quite strong.